2020
DOI: 10.5194/acp-20-3965-2020
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal contrast in size distributions and mixing state of black carbon and its association with PM<sub>1.0</sub> chemical composition from the eastern coast of India

Abstract: Abstract. Over the Indian region, aerosol absorption is considered to have a potential impact on the regional climate, monsoon and hydrological cycle. Black carbon (BC) is the dominant absorbing aerosol, whose absorption potential is determined mainly by its microphysical properties, including its concentration, size and mixing state with other aerosol components. The Indo-Gangetic Plain (IGP) is one of the regional aerosol hot spots with diverse sources, both natural and anthropogenic, but still the informati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 80 publications
1
30
0
Order By: Relevance
“…Recently, Ko et al (2020) compared the MMD and NMD values of rBC size distributions from different dominant sources. Previous studies report that the MMD (and NMD) values over the regions dominated by fresh fossil fuel emissions are smaller (MMD ∼ 100 to 178 nm and NMD ∼ 30 to 80 nm) compared to the areas with dominant solid-fuel sources (biomass, biofuel, coal-burning) (MMD ∼ 130 to 210 nm and NMD ∼ 100 to 140 nm), whereas well-aged and background BC particles in outflow regions have MMD values in between (MMD ∼ 180 to 225 nm and NMD ∼ 90 to 120 nm) (McMeeking et al, 2010;Liu et al, 2010Liu et al, , 2014Kondo et al, 2011;Cappa et al, 2012;Sahu et al, 2012;Metcalf et al, 2012;Laborde et al, 2013;Reddington et al, 2013;Gong et al, 2016;Raatikainen et al, 2017;Krasowsky et al, 2018;Brooks et al, 2019;Kompalli et al, 2020b;Ko et al, 2020). The spatial distribution of mass median diameter and number median diameters during the ICARB-2018 shown in Fig.…”
Section: Spatial Distribution Of Rbc Mass/number Concentrations and Size Distributionsmentioning
confidence: 99%
“…Recently, Ko et al (2020) compared the MMD and NMD values of rBC size distributions from different dominant sources. Previous studies report that the MMD (and NMD) values over the regions dominated by fresh fossil fuel emissions are smaller (MMD ∼ 100 to 178 nm and NMD ∼ 30 to 80 nm) compared to the areas with dominant solid-fuel sources (biomass, biofuel, coal-burning) (MMD ∼ 130 to 210 nm and NMD ∼ 100 to 140 nm), whereas well-aged and background BC particles in outflow regions have MMD values in between (MMD ∼ 180 to 225 nm and NMD ∼ 90 to 120 nm) (McMeeking et al, 2010;Liu et al, 2010Liu et al, , 2014Kondo et al, 2011;Cappa et al, 2012;Sahu et al, 2012;Metcalf et al, 2012;Laborde et al, 2013;Reddington et al, 2013;Gong et al, 2016;Raatikainen et al, 2017;Krasowsky et al, 2018;Brooks et al, 2019;Kompalli et al, 2020b;Ko et al, 2020). The spatial distribution of mass median diameter and number median diameters during the ICARB-2018 shown in Fig.…”
Section: Spatial Distribution Of Rbc Mass/number Concentrations and Size Distributionsmentioning
confidence: 99%
“…It is well-known that EC is directly emitted into the atmosphere as fine particle via incomplete combustion of fossil fuel and biomass burning whereas coarse mode EC may be associated with adsorption of water molecule to the surface of EC particles or coating by organic/inorganic acids during their long-range transport in the atmosphere, leading to substantial increase in the particle diameter. 57 A robust correlation (0.96) was found between EC and nss-K + in fine mode, implying that biomass burning is a major source in fine mode. It is also worthy to note that EC was strongly correlated with OC in fine mode (0.90), however no such correlation was observed in the coarse mode (−0.02).…”
Section: Resultsmentioning
confidence: 89%
“…In contrast, EC showed unimodal during April 2018 and Sept. 2018 and bimodal size distributions during Nov. 2017, Jan. 2017, and March 2019, although the prominent peak was observed in fine mode. It is well-known that EC is directly emitted into the atmosphere as fine particle via incomplete combustion of fossil fuel and biomass burning whereas coarse mode EC may be associated with adsorption of water molecule to the surface of EC particles or coating by organic/inorganic acids during their long-range transport in the atmosphere, leading to substantial increase in the particle diameter . A robust correlation (0.96) was found between EC and nss-K + in fine mode, implying that biomass burning is a major source in fine mode.…”
Section: Resultsmentioning
confidence: 94%
“…The association of BC with accumulation mode APs during continental conditions suggests that the carbonaceous APs existing in this size range can act as CCN. From the eastern coast of India, Kompalli et al (2020) have reported highly coated larger BC particles (> 110 nm) in dry conditions under the continental influence, while nascent BC particles (∼ 80 nm) with less coating were found during ISM due to wet scavenging. This finding is in line with the current marine-2 observations.…”
Section: Relationship Between Aerosol Absorption and Ccn Propertiesmentioning
confidence: 99%